Pengaruh Fasilitas Dan Promosi Terhadap Loyalitas Pelanggan Di Nm Recording Studio Kota Tangerang - Ade Rizky; Erlita Kurniawaty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
ABSTRACT This study aims to determine the effect of facilities and promotion on customer loyalty at NM Recording Studio, Tangerang City, both partially and simultaneously. The research method used is quantitative with an associative approach. The sampling technique applied was non-probability sampling with a saturated sample, in which the entire population of 57 respondents, consisting of customers who used the services of NM Recording Studio, was taken as the sample. The results show that facilities (X1) have a positive and significant effect on customer loyalty (Y) (t-count 18.310 > t-table 1.673, sig. 0.000 < 0.05), with the regression equation Y = -4.325 + 0.823X1, a very strong correlation (r = 0.927), and a contribution of 85.9% (R² = 0.859). Promotion (X2) also has a positive and significant effect (t-count 9.710 > t-table 1.673; sig. 0.000 < 0.05), with the regression equation Y = 1.139 + 0.792X2, a strong correlation (r = 0.795), and a contribution of 63.2% (R² = 0.632). Simultaneously, both variables have a significant effect (F-count 258.949 > F-table 3.17; sig. 0.000 < 0.05), with the regression equation Y = -5.339 + 0.641X1 + 0.296X2, a very strong correlation (r = 0.952), and a contribution of 90.6% (R² = 0.906).